Management of Patients with Acute Arterial Ischemia of the Lower Limb - Ergashev Ulugbek Yusufjanovich; Minavarkhojayev Ravshankhuja Rakhmatkhuja ogli; Malikov Nodir Muzaffar ugli; Ortiqboyev Farxod Dilshod ugli; Mukhamedova Shahnoza Yusufjon qizi (Scientific Trends, 2023)
To improve the diagnosis and optimize the surgical tactics for the treatment of patients with acute lower limb ischemia, severe limb ischemia, depending on the prognostic criteria for surgical treatment.
Keywords: acute arterial occlusion, atherosclerotic lesions of the arteries of the lower extremities.